The Analysis of Supply Chain Performance Measurement at Construction Project. (2015) - Wibowo, M. Agung; Sholeh, Moh Nur
Abstract: During recent years, supply chain has become a major subject of management research and manufacturing theory. The impact of various supply chain management practices on project performance has been measured through a combination of a survey and the development of simulation models. Supply chain performance measurement on the road project has not been much discussed much today. As it is known that the road project is one of the very high construction project roles. Performance measurement using the Supply Chain Operations References (SCOR) will analyze how the supply chain management of contractor. The aim of the study is to analyze supply chain performance in road projects. This measurement using the SCOR model as a Key Performance Indicator (KPI) is calculated using the weighted criteria Analytical Hierarchy Process (AHP). Weighting and measurement results were analyzed using Objectives Matrix (OMAX) and traffic light. The results of the analysis and the measurement of supply chain performance are medium score or good enough for road projects. The factors that leads to the success of this supply chain are the readiness of the contractor, supplier partners, supply chain strategy, and the ability of labors.